3D Printing and Section 512(c): Safe Harbor Provision of the Digital Millennium Copyright Act - Donald, L. Buresh (Journal of 3D Printing and Applications, 2019)
This paper addresses the topic of whether, and to what extent, copyrights should govern the distribution of 3D printing plans which are used in creating 3D printed, tangible objects. The essay discusses the various 3D printing technologies, describes how 3D printing is accomplished, defines copyright, and then briefly outlines the Digital Millennium Copyright Act (“DMCA”) of 1998. In particular, the paper lists the conditions that a firm publishing 3D printing plans must satisfy to invoke Section 512(c) safe harbor provision of the DMCA. Finally, the essay discusses when a distributor of 3D printing plans would be protected under the safe harbor provisions, arguing that when a 3D printing plan is released not-for-profit, the organization is protected under Section 512(c).
Keywords: Copyrights; 3D Printing; Digital Millennium Copyright Act; Section 512(c) Safe Harbor Provision